1987
DOI: 10.1577/1548-8659(1987)116<79:tfacci>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Frequencies and Contaminant Concentrations in Brown Bullheads from an Industrialized River and a Recreational Lake

Abstract: Frequencies of external and grossly visible liver tumors were high in brown bullheads Ictalurus nebulosus from Black River, an industrialized Lake Erie tributary. Skin and liver tumors were lacking in brown bullheads from Buckeye Lake, a reference site, and the incidence of lip tumors was low (<2%). Liver tumors, primarily cholangiocarcinomas, increased significantly (P < 0.05) with age in Black River brown bullheads, occurring in 28–44% of the 4‐year‐old fish collected in 1980–1982. External tumors did not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 13 publications
1
44
1
1
Order By: Relevance
“…Baumann et al (1987) demonstrated an increased frequency of liver tumours with age in brown bullheads Ictalurus nebulosus and also that 4 to 5 yr old fish had a significantly higher prevalence of biliary carcinomas than 2 to 3 yr old ones collected at the same site (Baumann et al 1990). Furthermore, the latter study demonstrated a relative lack (or even absence) of fish of age ≥ 5 yr at sites with the highest liver tumour prevalence, suggesting an age-selective mortality associated with the disease (Baumann et al 1990).…”
Section: Introductionmentioning
confidence: 66%
“…Baumann et al (1987) demonstrated an increased frequency of liver tumours with age in brown bullheads Ictalurus nebulosus and also that 4 to 5 yr old fish had a significantly higher prevalence of biliary carcinomas than 2 to 3 yr old ones collected at the same site (Baumann et al 1990). Furthermore, the latter study demonstrated a relative lack (or even absence) of fish of age ≥ 5 yr at sites with the highest liver tumour prevalence, suggesting an age-selective mortality associated with the disease (Baumann et al 1990).…”
Section: Introductionmentioning
confidence: 66%
“…Associations between contaminant levels and neoplastic diseases have been made in several aquatic species (13)(14)(15)(16)(17)(18) (20,21). Similarly, a wide variety of chemical contaminants are known to disrupt immune system functions (22)(23)(24).…”
Section: Do Environmental Contaminants Play a Role In Gtfp?mentioning
confidence: 99%
“…Bile from such bullheads exhibits fluorescent metabolites resulting from the metabolism ofPAHs (18). Baumann has suggested that PAHs are the most likely carcinogens to be responsible for the high rate ofliver tumors in brown bullheads in contaminated environments (19 (20).…”
Section: Effects Of Pahs On Aquatic Organismsmentioning
confidence: 99%